Factor structure and validation of the mental health checklist (MHCL) for use in isolated, confined and extreme environments. (August 2019) - Bower, Joanne L.; Laughlin, Mitzi S.; Connaboy, Christopher; Simpson, Richard J.; Alfano, Candice A.
Abstract: Although human psychological risks gravely threaten the safety and success of future Mars missions, current knowledge of the mental health problems most likely to manifest during long duration space exploration (LDSE) is surprisingly inadequate. Previous research conducted during spaceflight and in analog settings has produced discrepant, sometimes contradictory findings and relied on measures that have not been validated for use in extreme environments, where the number, intensity, and duration of stressors exceed typical human experience. We therefore developed the Mental Health Checklist (MHCL) based on subject matter interviews and comprehensive literature reviews. In study one, exploratory and confirmatory factor analyses resulted in 3 reliable subscales ( positive adaptation, poor self-regulation, and anxious apprehension ) explaining 53% of the total variance. In study two, we examined the reliability and convergent validity of the MHCL in large sample of participants stationed in Antarctica. Findings suggest the MHCL to have acceptable psychometric properties for use in extreme settings. We encourage other researchers to incorporate the MHCL in future studies, including spaceflight research, and to examine its sensitivity for capturing intra-individual symptom changes over time. Highlights: Psychological factors impact safety in extreme environments (e.g., spaceflight). We created a reliable measure assessing psychological risk in extreme environments. The MHCL assesses positive and negative emotion and associated psychological states. It showed good reliability and model fit in community and Antarctic participants. Associations with other emotion regulation scales demonstrate convergent validity.